2019
DOI: 10.1042/bsr20182423
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between GDF5 gene polymorphisms and environment factors increased the risk of knee osteoarthritis: a case–control study

Abstract: Using a case–control design, we assessed the association between single nucleotide polymorphisms (SNPs) of growth and differentiation factor 5 (GDF5)/rs143383 gene and interaction with environments and knee osteoarthritis (KOA). We recruited 288 KOA patients from the First Clinical College, Henan University of Chinese Medicine between June 2017 and May 2018. There was significant difference in genotype distribution between case group and control group (χ2 = 22.661, P=0.000). The minor C allele was significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…On the one hand, previous literatures have said that GDF 5 rs143383 polymorphisms C allele is a protective factor for the susceptibility of knee osteoarthritis among Caucasian populations (OR=0.74, P<0.001) and Asian populations (OR=0.87, P=0.004) [9]. On the other hand, Sujie Zhang et al holds that interaction GDF 5 rs143383 polymorphisms T allele increases the risk of knee osteoarthritis among Asian (OR=1.62, P<0.001) [5]. But now our research shows that GDF 5 rs143383 polymorphisms are only relate to knee osteoarthritis among Caucasian populations by subgroup analysis, not Asian populations.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…On the one hand, previous literatures have said that GDF 5 rs143383 polymorphisms C allele is a protective factor for the susceptibility of knee osteoarthritis among Caucasian populations (OR=0.74, P<0.001) and Asian populations (OR=0.87, P=0.004) [9]. On the other hand, Sujie Zhang et al holds that interaction GDF 5 rs143383 polymorphisms T allele increases the risk of knee osteoarthritis among Asian (OR=1.62, P<0.001) [5]. But now our research shows that GDF 5 rs143383 polymorphisms are only relate to knee osteoarthritis among Caucasian populations by subgroup analysis, not Asian populations.…”
Section: Discussionmentioning
confidence: 97%
“…Sixteen articles [5,11,[15][16][17][18][19][20][21][22][23][24][25][26][27][28], including separate 20 studies (7997 cases and 12684 controls), finally have collected in the meta-analysis from 196 studies, which process is showed in Fig 1. All studies' details, including first author name; year of publication; ethnicity; country; sex; gender ration; evaluation of quality (NOS); HWE; study design; genotyping method and mean age, put into the Table 1.…”
Section: Studies Extraction and Characteristics Of Studiesmentioning
confidence: 99%
“…Knee osteoarthritis is a multi-factorial disease, and its pathogenesis is currently unclear. Current studies have shown that smoking, diet, exercise, and genes are all associated with osteoarthritis [5]. The diagnosis of knee osteoarthritis is currently mainly diagnosed by imaging.…”
Section: Introductionmentioning
confidence: 99%
“…Growth differentiation factor 5 (GDF5) rs143383 genetic polymorphisms is the association of the susceptibility of knee osteoarthritis reported in Bioscience Reports [5]. GDF5, also known as cartilage derived morphogenetic protein 1 (CDMP1), is an extracellular signaling molecule that participates in the development maintenance and repair of bone, cartilage, and other tissues of the synovial joint, with penetrant and rare deleterious mutations of the GDF5 gene resulting in dominant skeletal defects [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation